Bunburra Rockhole: Exploring the geology of a new differentiated asteroid. (1st July 2017) - Benedix, G.K.; Bland, P.A.; Friedrich, J.M.; Mittlefehldt, D.W.; Sanborn, M.E.; Yin, Q.-Z.; Greenwood, R.C.; Franchi, I.A.; Bevan, A.W.R.; Towner, M.C.; Perrotta, G.C.; Mertzman, S.A.
Abstract: Bunburra Rockhole is the first recovered meteorite of the Desert Fireball Network. We expanded a bulk chemical study of the Bunburra Rockhole meteorite to include major, minor and trace element analyses, as well as oxygen and chromium isotopes, in several different pieces of the meteorite. This was to determine the extent of chemical heterogeneity and constrain the origin of the meteorite. Minor and trace element analyses in all pieces are exactly on the basaltic eucrite trend. Major element analyses show a slight deviation from basaltic eucrite compositions, but not in any systematic pattern. New oxygen isotope analyses on 23 pieces of Bunburra Rockhole shows large variation in both δ 17 O and δ 18 O, and both are well outside the HED parent body fractionation line. We present the first Cr isotope results of this rock, which are also distinct from HEDs. Detailed computed tomographic scanning and back-scattered electron mapping do not indicate the presence of any other meteoritic contaminant (contamination is also unlikely based on trace element chemistry). We therefore conclude that Bunburra Rockhole represents a sample of a new differentiated asteroid, one that may have more variable oxygen isotopic compositions than 4 Vesta. The fact that Bunburra Rockhole chemistry falls on the eucrite trend perhaps suggests that multiple objects with basaltic crusts accreted in a similar region of the Solar System.